FEASIBILITY STUDY OF PARK AND RIDE IN ALUN-ALUN BEKASI CITY - Maulana, Aldy; Murtejo, Tedy; Rulhendri, Rulhendri; Alimuddin, Alimuddin; Chayati, Nurul (Universitas Ibn Khaldun Bogor, 2021)
The efforts of the Bekasi City government to reduce congestion and make it easier for the community to mobilize to DKI Jakarta by implementing the Park and Ride concept, in this case the Bekasi City government plans to build a Park and Ride facility in the Bekasi City square. This research was conducted to determine the feasibility level of the Park and Ride development plan in the Bekasi City square and also to obtain an overview of the existing results of the traffic conditions in the Bekasi City square area (PMI Tennis Court). The traffic counting survey and interviews were conducted at Bekasi Station, on Jalan Ir. H juanda, Jalan Perjuangan, Jalan Pramuka and Jalan Veteran which are then processed using Microsoft Excel to find out the maximum demand from Park and Ride, namely 1527 motorbikes and 308 units of cars, the economic feasibility level of the Park and Ride building shows an IRR of 3.4% , the NPV value> 1 is IDR 102,280,883,874.40 and BCR is 1.37. With a prediction of a building length of 25 years, while for roads that become accessibility for vehicles to and from the Park and Ride building, the lowest level of service occurs on Veteran and Pramuka roads, with service levels F and E. This proves that traffic engineering is necessary. and increasing road capacity, to and from Park and Ride, with pedestrian access and bicycle lanes (to improve road performance).